2022
DOI: 10.21203/rs.3.rs-2126376/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Work-Related Stress, Quality of Life, and Coping Mechanism Among Lecturers in a Tertiary Educational Institution in Anambra State, Nigeria

Abstract: Work-related stress (WRS) is a highly prevalent and pervasive problem that can result in loss of productivity and deterioration of lecturer’s health. Lecturing work requires coping with some of the stressful situations found in any workplace. The study determined the work-related stress, coping mechanisms, and quality of life among lecturers at Nnamdi Azikiwe University (NAU). Method:This was a cross-sectional survey involving 283 lecturers consecutively recruited from NAU. The Health and Safety Executive W… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…51 These studies, which reported disaggregated results, were conducted exclusively in Ethiopia and Nigeria, employing cross-sectional and randomised trial designs, respectively. According to the primary findings, Chukwuemeka and colleagues asserted that work-related stress is not influenced by gender, 53 while Kabito and colleagues highlighted that stress predominantly arises from role ambiguity and gender factors. 54 Nevertheless, it is evident that academics do encounter work-related stress.…”
Section: Table 1 Data Chartingmentioning
confidence: 99%
See 1 more Smart Citation
“…51 These studies, which reported disaggregated results, were conducted exclusively in Ethiopia and Nigeria, employing cross-sectional and randomised trial designs, respectively. According to the primary findings, Chukwuemeka and colleagues asserted that work-related stress is not influenced by gender, 53 while Kabito and colleagues highlighted that stress predominantly arises from role ambiguity and gender factors. 54 Nevertheless, it is evident that academics do encounter work-related stress.…”
Section: Table 1 Data Chartingmentioning
confidence: 99%
“…When grappling with work-related stress, some academics tend to attribute blame to themselves. 55 Amid these challenges, academics turn to substance use as a coping mechanism, while others seek emotional support.…”
Section: Table 1 Data Chartingmentioning
confidence: 99%
“…Below are the monthly salaries of the different categories of lecturers after the normal deductions. Graduate Assistant with first class or second class upper may be pegged at N 99,768; Assistant Lecturer with a Master's Degree, N 114,464; Lecturer II, N 130,003; Lecturer I with a PhD, N 163,709; Senior Lecturer with a PhD and at least eight years lecturing experience, N 231,393; Reader/Associate professor with at least twelve years lecturing experience, having various publications and a PhD, N 281,867; and a Professor who has at least fifteen years' experience and equally many publications has an average salary of N 342,442 (Chukwuemeka, 2024).…”
Section: Lecturers' Salary (Ls)mentioning
confidence: 99%